Volume 8A: Heat Transfer and Thermal Engineering 2015
DOI: 10.1115/imece2015-52879
|View full text |Cite
|
Sign up to set email alerts
|

Improved Thermal Comfort of Office Occupants Through Better Air Diffuser Designs

Abstract: In this work we are exploring the influence of the design of air diffusers on a number of parameters that influence the thermal comfort of building occupants. In particular we are looking at calculating the Air Diffusion Performance Index (ADPI) and vertical temperature difference as well as the throw and drop parameters for various diffuser designs. The results show that while a complex radial vane diffuser that uses the Coanda effect could offer good performance if the HVAC system is used for cooling, the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The result showed that the effectiveness of the cooling tower improve by 8.74 %. Liu et.al 9) compared the impact of the design of a multi-cone diffuser with that of a complex radial vane air diffuser, based on thermal comfort inside the building. Parameters like vertical temperature and Air Diffusion Performance Index were considered in the study.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the effectiveness of the cooling tower improve by 8.74 %. Liu et.al 9) compared the impact of the design of a multi-cone diffuser with that of a complex radial vane air diffuser, based on thermal comfort inside the building. Parameters like vertical temperature and Air Diffusion Performance Index were considered in the study.…”
Section: Introductionmentioning
confidence: 99%